Investigation on the Dynamic Behavior of Rock in Three Stages of Rock Fragmentation Under Vibro-Impact Condition: Continuum and Discontinuum Model - Zhao Zhang; Zewen Gu; Jianlin Liu (Advances in Civil Engineering)
Understanding the effects of harmonic excitation on rock failure is essential in terms of enhancing rock-breaking efficiency. Although a series of dynamic cracking have been studied, investigations on the dynamic behavior of rock in different stages of rock fragmentation under practical vibro-impact drilling conditions are limited. In the present work, the continuum model and discontinuum model are proposed, respectively, which can be used to explore the influences of elastic waves and resonance effect in different stages. First, before rock fragmentation, damping effect on the attenuation of waves in continuum rock is investigated, where the parameters N and Nd are proposed to reflect the sustainability of dynamic influence of waves within the effective propagation distance α−1. Subsequently, in the early stage of rock fragmentation, the number and morphology of crack propagation under different excitation frequencies, penetration depths are obtained by using discrete element method (DEM). Next, in the late stage of rock fragmentation when the rock is regarded as a discontinuum separated by structural surfaces, the low-frequency resonance effect on rock breaking is studied based on a system with great stiffness disparity (SGSD). The theoretical results are verified by the experimental results based on the practical drilling with a multidimensional impactor. The results show that the dynamic influence of high or low excitation frequencies on rock fracture is quite different. The impact of excitation frequencies plays an important role in early and late stages of rock fragmentation to improve the rock-breaking efficiency. These findings contribute to a better understanding of the rock breaking mechanism under dynamic loads with certain excitation frequencies.